Natural convection solar air heater: Bell-mouth integrated converging channel for high flow applications - Singh A.P.; Kumar A.; Akshayveer; Singh O.P. (My University, 2025)
The bulk movement of fluid in natural convection solar air heater (SAH) is generated due to density variation and hence suffers from lower mass flow rates. Mounting additional surfaces/fins in SAH duct enhances the thermal characteristics, however, it comes at the cost of hydraulic performance. This limits the device usage in buildings and other high flow rate applications. In the present study, two new designs of SAH were numerically analyzed are: (a) taper flow passage for better thermal performance; (b) tapered designs incorporated with bell-mouth inlet opening for improved hydraulic performance. Parametric design analysis was conducted for large range of taper ratio and bell-mouth ratio. The results show that the tapered design is about 70% thermally more effective and about 6% higher Nusselt number per unit pressure drop than conventional SAH. A significant enhancement in hydraulic performance of more than 300% was observed when bell-shaped inlet design was integrated with the tapered designs. An independent correlation for Nusselt number variation has been developed as a function of Rayleigh number and tapper ratio. Predictions from the developed correlation is in excellent following with the numerical data. © 2020 Elsevier Ltd